Effects of immunosuppressive drugs on human adipose tissue metabolism - Pereira, Maria J. (2014)
Tese de doutoramento, Philosophy (Medicine), Institute of Medicine, Department of Molecular and Clinical Medicine, University of Gothenburg, Sahlgrenska Academy, 2012